Thinking with Balibar : A Lexicon of Conceptual Practice (Idiom (Fordham University Press), 2020)
This volume, the first sustained critical work on the French political philosopher Étienne Balibar, collects essays by sixteen prominent philosophers, psychoanalysts, anthropologists, sociologists, and literary critics who each identify, define, and explore a central concept in Balibar's thought. The result is a hybrid lexicon-engagement that makes clear the depth and importance of Balibar's contribution to the most urgent topics in contemporary thought. The book shows the continuing vitality of materialist thought across the humanities and social sciences and will be fundamental for understanding the philosophical bases of the contemporary left critique of globalization, neoliberalism, and the articulation of race, racism, and economic exploitation.